(untitled) - Kohsaka, Akira (New York, N.Y., 2004)
This edited volume examines the flaws in the Washington Consensus. The missing link identified is the relationship between market and government. The East Asian Miracle showed that the market and government are complementary, particularly with regard to economic development. However, the nature of this relationship has not been fully clarified. This book assesses development strategies and policy issues in the context of individual and/or regional economy's history and political-economic reality. The relationship may be conditional to these two factors. With these perceptions in mind, the book focuses on the role and significance of government in economic development in pursuit for new development strategies.
Keywords: Economic development,Globalization,Developing countries; Political aspects,Economic aspects,Economic policy